Extending UML for modeling Web applications - Baresi, L.; Garzotto, F.; Paolini, P. (34th Annual Hawaii International Conference on System Sciences (HICSS '01), 2001)
Web sites are progressively evolving from browsable, read-only information repositories to Web-based distributed applications. Compared to traditional Web sites, these Web applications do not only support navigation and browsing, but also operations that affect their contents and navigation states. Compared to traditional applications Web applications integrate operations with the built-in browsing capabilities of hypermedia. These novelties make Web application design a complex task that requires the integration of methods and techniques developed in different "worlds". This integration is achieved in this paper by extending and customizing the Unified Modeling Language (UML) with Web design concepts borrowed from the Hypermedia Design Model (HDM). Hypermedia elements are described through appropriate UML stereotypes. UML diagrams are also tailored to model operations and relate them with hypermedia elements. The approach is exemplified by describing the design of a Web-based conference manager.